2023
DOI: 10.1002/adom.202300195
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency and Narrow‐Band Near‐Ultraviolet Emitters with Low CIEy of 0.03 by Incorporating Extra Weak Charge Transfer Channel into Multi‐Resonance Skeleton

Abstract: Hybridized local and charge‐transfer (HLCT) excited‐state emitters can effectively utilize non‐radiative triplet excitons through high‐lying reverse intersystem crossing (hRISC), but they are mostly limited to the donor‐π‐acceptor type molecules. It is a great challenge to develop high‐performance near‐ultraviolet (NUV) emitters with narrow‐band emission by HLCT due to the large carrier injection barriers and high triplet energy. In this work, by incorporating planar multi‐resonance (MR) skeleton of oxygen‐bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Adapting the hot exciton concept can expand the candidates in designing fluorescent emitters for OLED applications. For example, recently, even MR-TADF emitters with hRISC processes have been reported [128][129][130][131]. This means that we need to expand our focal points beyond the conventional S 1 -T 1 energy gap.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting the hot exciton concept can expand the candidates in designing fluorescent emitters for OLED applications. For example, recently, even MR-TADF emitters with hRISC processes have been reported [128][129][130][131]. This means that we need to expand our focal points beyond the conventional S 1 -T 1 energy gap.…”
Section: Discussionmentioning
confidence: 99%
“…31 Gan et al reported a maximum EQE of 9.15% with the EL peak at 414 nm and a CIE y of 0.034 in the doped device with a doping concentration of 5 wt%. 26 Zhang et al and Chen et al realized maximum EQEs of 10.79% and 8.2% with CIE coordinates of (0.161, 0.031) and (0.161, 0.034) for carbazole-based emitters (2BuCzCNCz and POPCN-2CP) in the doped devices, while the EQEs were down to 5.24% and 7.5% with large FWHMs of 62 and 52 nm in the non-doped OLEDs. 32,33 Although the host–guest doping strategy can mitigate spectral redshift and enhance PL efficiency to a certain extent, such doped devices often face challenges such as potential phase separation issues, elevated processing costs, and the difficulty in selecting appropriate host materials.…”
Section: Introductionmentioning
confidence: 96%
“…11,12 Although some efforts have been made via rational molecular design or device engineering, external quantum efficiencies (EQEs) usually lie below 7% in simple non-doped NUV-OLEDs. 3,13–28 Moreover, most of the NUV-OLEDs suffer from serious efficiency roll-off at a high luminance level and poor color purity (the full width at half maximum (FWHM) value exceeding 50 nm), due to the intermolecular aggregation, strong intramolecular charge transfer (CT) effect, and unbalanced carrier injection, transport, and recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Zhu and co-workers reported two emitters, tBOSi and tBOSiCz, that displayed excellent near-UV emission properties, with emission peaks nearing 410 nm and the FWHM approaching only 30 nm. 36 The emission of tBOSi and tBOSiCz exhibits HLCT emission characteristics, demonstrating that triarylboron structures can serve as excellent acceptors for hot exciton emitters and are well suited for the construction of narrow-band and deep-blue OLEDs. Therefore, we expect that the combination of a rigid DOBNA with weak acceptor properties and anthracene will lead to a high-efficiency and high-colour purity deep-blue hot exciton emitter.…”
Section: Introductionmentioning
confidence: 99%